Determinan Pencegahan Kecurangan dalam Pengelolaan Dana Desa di Kecamatan Pelaihari Kabupaten Tanah Laut - Astia Putriana; Bella Puspita Rininda; Desy Amelia; Ines Saraswati Machfiroh; Yasir Hadiani; Yuli Fitriyani; M. Riduan Abdillah (Politeknik Ganesha Medan, 2026)
The purpose of this study was to examine how the competence, accountability, and transparency of village officials influence their ability to prevent fraud in village fund management. This study involved village officials in Pelaihari Regency. Purposive sampling resulted in 75 respondents. This study collected data through questionnaires. Data analysis techniques used included descriptive statistical analysis, data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that the competence and transparency of village officials did not influence fraud prevention, while accountability did. This suggests that fraud prevention efforts in village fund management are more effective if implemented through increased accountability of village officials, such as regular reporting, clear accountability, and consistent oversight of every use of village funds. Previous research has emphasized fraud detection, while prevention mechanisms at the village level are still limited. This study contributes by developing a fraud prevention model based on the Fraud Diamond in the context of village fund governance. These findings provide practical implications that local governments and policymakers need to emphasize strengthening accountability and monitoring mechanisms as a primary strategy in preventing fraud and improving the quality of village financial governance.